Effect of a biosynthetic bacterial 6-phytase on the digestibility of phosphorus and phytate in midlactating dairy cows. (27th January 2023) - Dersjant-Li, Yueming; Kok, Ivonne; Westreicher-Kristen, Edwin; García-González, Rubén; Mereu, Alessandro; Christensen, Trine; Marchal, Leon
Abstract: The effect of a biosynthetic bacterial 6-phytase (PhyG) on the digestibility and excretion of crude protein (CP), phosphorus (P), and phytate-P (PP) in midlactating dairy cows was investigated. Thirty Holstein-Friesians were assigned to three treatments with 10 cows per treatment in a randomized block design. Cows were fed forage (grass and corn silage) provided ad libitum, and a concentrate (without added inorganic phosphate) administered separately in amounts individualized per cow according to milk production, supplemented with phytase according to treatment. The formulated forage-to-concentrate-ratio was 65%:35%. Dietary treatments comprised the control diet (CON) and CON supplemented with 2, 000 (PhyG2, 000) or 5, 000 (PhyG5, 000) phytase units (FTU)/kg DM in the total diet. The experiment comprised an 18-d preperiod for the collection of data to facilitate the allocation of cows to the treatments, followed by a 19-d experimental period comprising a 14-d diet adaptation period and 5 d of twice daily feces collection. Fecal samples were analyzed for the determination of apparent total tract digestibility (ATTD) of chemical constituents in the diet. The ATTD of PP was 92.6% in CON suggesting a high but incomplete degradation of phytate by ruminal microbial phytases. Cows fed PhyG2, 000 exhibited increased ATTD of CP and PP [68.4% (2.7% points above CON) and 95.1% (2.5% points above CON), respectively] whilst PhyG5, 000 further increased ATTD PP and also increased ATTD P [54.1% (7.8% points above CON)]; ATTD of Ca tended to be increased in PhyG5, 000 vs. CON. Linear dose–response relationships were observed for ATTD of DM, CP, P, Ca, and PP. In addition, fecal excretion of P, and PP linearly reduced and that of Ca and CP tended to linearly reduce with increasing PhyG dose level. No difference was observed for DM intake and milk composition was unaffected except for milk protein which tended to be higher in cows fed PhyG5, 000 than CON. In summary, the addition of exogenous phytase at 2, 000 FTU/kg or higher to diets of lactating dairy cows improved P, PP, Ca, and CP digestibility and reduced fecal excretion of P, PP, and CP in a dose-dependent manner. Abstract : An exogenous phytase supplemented to a commercially relevant diet of low phosphorus content is found to be effective in improving phosphorus and protein digestibility and reducing their excretion in midlactating dairy cows. Dietary supplementation with phytase offers an important approach to optimizing nutrient balance and reducing environmental phosphorus and nitrogen pollution from dairy farms. Lay Summary: Traditionally, it has been believed that dairy cows are able to fully utilize the phosphorus (P ) in feed, including that from plant-derived phytate, because of phytase activity of bacteria in the rumen. However, recent data have shown otherwise. This study investigated the effect of a biosynthetic bacterial 6-phytase supplemented to the diets of midlactating dairy cows on the digestibility and excretion of phosphorus and other key nutrients, over a 19-d experimental period. The experimental diets were commercially relevant in composition and low in phosphorus. At either or both of two tested dose levels (2, 000 and 5, 000 phytase units (FTU) per kilogram DM in the total diet), the exogenous phytase increased the digestibility and reduced fecal excretion of crude protein (CP), total P, and phytate-P compared with a comparable unsupplemented diet. The increases in CP, PP, and P digestibility were phytase-dose dependent. In addition, at the highest dose level, the phytase tended to increase the protein content of milk. The findings indicate that the use of exogenous phytase can improve P and protein utilization in dairy cows and offers an important approach to optimizing nutrient balance and reducing environmental P and nitrogen (N) pollution from dairy farms.